A basic insight into COVID-19 vaccines: an overview - Khan, Sarfaraz Alam; Siddiqui, Nazeem Ishrat (International Journal of Basic & Clinical Pharmacology, 2023)
Atypical serious respiratory illnesses were reported in December 2019 from Wuhan, a city of China, which later spread to other places rapidly and became a global pandemic. Soon it was discovered to be caused by a novel corona virus, named as the severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) and the disease caused by it as corona virus disease-19 (COVID-19). Since COVID-19 is a new viral disease, world is still struggling to find out a permanent remedy to overcome this serious health problem. Developing safe and effective vaccine against SARS-CoV-2 has become the only way forward to tackle it. Various vaccines have been developed and are approved for mass vaccination on emergency basis. Both classical and next generation vaccine platforms are being used to develop COVID-19 vaccine. It seems interesting to have a look on the various types of vaccines and get an insight into them so that we can get familiarize with the COVID-19 vaccination.